Epilepsy in Adolescents: Rational Treatment and Considerations - Sharp, Gregory B. (Journal of Pediatric Epilepsy, 2015)
Human brain development is a dynamic process that proceeds from childhood through the adolescent period into adulthood both anatomically and functionally. Likewise, epilepsy follows a course of change. Childhood seizure disorders may change or remit, and other epilepsies may begin during adolescence. Care of the epilepsy patient should include new or further diagnostic testing that is appropriate for the individual patient, differentiation from other paroxysmal disorders, attention to psychosocial and behavioral concerns, and selection and management of appropriate antiepileptic drug therapy. Attention should also be placed on potential adverse effects that appropriate antiepileptic drugs may impart. Special consideration should be given to adolescent girls who should be considered of childbearing age during adolescence. When epilepsy is refractory to medical therapy, alternative therapies should be considered that include epilepsy surgery, vagus nerve stimulation, and specific diets such as ketogenic diet and modified Atkins diet that can be used to successfully treat epilepsy.
Keywords: adolescents; epilepsy; antiepileptic drugs